Kingdom of the Netherlands : Aruba; 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands -Aruba. (IMF Staff Country Reports; Country Report ;, 2008)
Aruba is one of the most developed islands in the Caribbean. Still, it is vulnerable to external shocks owing to its heavy dependence on tourism and a steady increase in public debt. Policies to support further fiscal consolidation and boost Aruba's growth potential are needed. Maintaining macroeconomic stability will require fiscal adjustment and an appropriately tight monetary policy. Bolstering the growth potential will require creating the right conditions for private investment and diversification. The financial system is generally sound, but warrants continued supervisory vigilance.